Kualitas internal telur ayam ras MB 402 yang diberi tepung bawang putih (allium sativum l) sebagai feed additive dalam ransum - Leke, J.R.; Sompie, F.N.; Nangoy, F.J.; Haedar, B.; Sondakh, E.H.B. (ZOOTEC, 2021)
INTERNAL QUALITY OF MB 402 CHICKEN EGG FED GARLIC FLOUR (Allium sativum L) AS FEED ADDITIVE IN THE RATION. Â This study aims to determine the internal quality of chicken eggs of MB 402 fed garlic flour (Allium sativum l) as a feed additive in the ration. Eggs are one of the livestock products that have high nutritional value and are complete, at a relatively cheap price. Garlic contains active compounds making it a potential feed additive. The goals of feed additives are the health of livestock, increase production and productivity, reduce mortality, fulfill chicken nutrition, and increase growth acceleration (growth promoter). This research has been carried out at the CV Gunawan Farm for 6 weeks. The research material used 100 laying hens with 5 treatments and 5 replications and each replication was occupied by 4 laying hens. The design used was a completely randomized design, if there are differences, continue with Duncan's Multiple Range Test. The treatment arrangements used were as follows: R0 = 100% basal ration (RB); R1 = RB + 1% TBP flour; R2 = RB + 2% TBP flour; R3 = RB + 3% TBP flour; R4 = RB + 4% TBP flour. Based on the results of data analysis and discussion for all variables, that the treatment of garlic flour up to 4% in the ration of laying hens had no significant effect (P> 0.05) on the egg white index and egg yolk index, but had a very significant effect (P <0.01) on the yolk color. Based on the results of data analysis and discussion of all variables, it is concluded that giving garlic flour up to 4 percent can improve egg quality.Keywords: internal quality of eggs, garlic (Allium sativum l)